Management of radicular cyst associated with primary teeth using decompression: a retrospective study - Jun Pei; Shimin Zhao; Hui Chen; Jun Wang (BMC, 2022)
Abstract Background Radicular cysts arising from primary teeth are rare. Enucleation and marsupialization or decompression are treatment approach to odontogenic cysts. Decompression known to achieve good results in various cysts is widely used in clinic. This study aims to evaluate the efficiency of decompression in reducing radicular cysts associated with primary teeth in children. Methods Cases of radicular cysts associated with primary teeth treated by decompression were reviewed in the present study. Clinical information and radiologic data of pre and post decompression were measured and analyzed. Results Twenty-three patients treated for 25 cysts were included. All lesions with mean initial area 3.66 ± 2.00 cm2 were reduced after decompression time ranging 2 to 10 months. Mean rate of reduction was 0.77 ± 0.44 cm2/mo and large lesions (> 3.5 cm2) had a significantly higher reduction rate compared to smaller ones (< 3.5 cm2) (P < 0.00). All effected succedaneous teeth erupted after treatment at follow-up while 12 (46%) of them had root development problems. Conclusions Decompression represents superiority as an effective and less invasive treatment in radicular cysts associated with primary teeth. Trial registration: This study was retrospectively registered in the Ethics Committee of Ninth People's Hospital Affiliated with Shanghai JiaoTong University School of Medicine (No.SH9H-2022-T158-1).